EP4 receptor as a new target for bronchodilator therapy. Issue 12 (23rd May 2011) - Buckley, James; Birrell, Mark A; Maher, Sarah A; Nials, Anthony T; Clarke, Deborah L; Belvisi, Maria G
Abstract : Background: Asthma and chronic obstructive pulmonary disease are airway inflammatory diseases characterised by airflow obstruction. Currently approved bronchodilators such as long-acting β2 adrenoceptor agonists are the mainstay treatments but often fail to relieve symptoms of chronic obstructive pulmonary disease and severe asthma and safety concerns have been raised over long-term use. The aim of the study was to identify the receptor involved in prostaglandin E2 (PGE2 )-induced relaxation in guinea pig, murine, monkey, rat and human airways in vitro . Methods: Using an extensive range of pharmacological tools, the relaxant potential of PGE2 and selective agonists for the EP1–4 receptors in the presence and absence of selective antagonists in guinea pig, murine, monkey, rat and human isolated airways was investigated. Results: In agreement with previous studies, it was found that the EP2 receptor mediates PGE2 -induced relaxation of guinea pig, murine and monkey trachea and that the EP4 receptor mediates PGE2 -induced relaxation of the rat trachea. These data have been confirmed in murine airways from EP2 receptor-deficient mice ( Ptger2 ). In contrast to previous publications, a role for the EP4 receptor in relaxant responses in human airways in vitro was found. Relaxant activity of AH13205 (EP2 agonist) was also demonstrated in guinea pig but not human airway tissue, which may explain its failure in clinical studies. Conclusion: Identification of the receptor mediating PGE2 -induced relaxation represents a key step in developing a novel bronchodilator therapy. These data explain the lack of bronchodilator activity observed with selective EP2 receptor agonists in clinical studies.